Peer Feedback in Academic Writing: Students' Perspectives on Learning and Improvement - Neni Nurkhamidah; Ninuk Lustyantie; Uwes Anis Chaeruman (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
Peer feedback in academic writing classes has gained considerable attention for its potential to enhance students' writing abilities, critical thinking, and engagement in learning. This study investigates students' perceptions of peer feedback in an Academic Writing course at MNC University. Using a qualitative case study approach, data were collected through interviews with seven students to gain in-depth insights into their experiences. The findings reveal that while most students view peer feedback as a valuable tool for improving writing skills, fostering collaboration, and encouraging critical reflection, others express concerns about confidence and feedback quality. Specifically, nearly half of the participants reported feeling unsure about their ability to provide effective feedback, and several noted the lack of clarity in the feedback they received. These findings underscore the importance of providing clearer guidelines on giving and implementing feedback. By addressing these challenges, instructors can foster stronger collaboration, enhance self-assessment skills, and boost engagement in the writing process. Structured peer feedback, when integrated effectively, can create a more interactive and reflective learning environment, ultimately contributing to improved writing performance and broader educational goals.